Fast electrochemical reactions during the anodization of platinum electrodes in aqueous solutions : Detection of a reversible charge storage process at platinum-oxide-coated electrodes - Bolzán, Agustín Eduardo (1992)
Fast electrochemical reactions at platinum and platinum-oxide-coated electrodes immersed in aqueous electrolytes can be observed by means of the triangularly modulated triangular potential sweep technique. The surface redox process commences at about 0.75 V in acid solution and is related to the initial oxygen-containing species reversibly electroadsorbed on platinum. Platinum coated with an oxide layer formed through a potentiodynamic routine presents a reversible charge storage process at about 1.6 V in acid solution. The corresponding reaction can be interpreted as a reversible redox couple involving Pt(II)-Pt(IV) and proton injection in the platinum oxide matrix. The charge contribution of the second redox system is smaller than the total oxide charge accumulated on the substrate. Both fast redox systems appear also in base solutions.